INOVASI LAYANAN KEUANGAN DIGITAL (FINTECH) SEBAGAI PENDUKUNG PERTUMBUHAN E- COMMERCE : KAJIAN LITERATUR - Nurul Ramandini; Hikmah Dzil Hijjah; Arsalan Bintang Romadi (Media Riset Bisnis Manajemen Akuntansi, 2025)
The rapid growth of financial technology (fintech) has significantly supported the expansion of e-commerce. This literature review explores how fintech innovations—such as digital wallets, online payments, and digital lending—enhance transaction efficiency, increase consumer trust, and support small businesses in online markets. Findings indicate a strong synergy between fintech and e-commerce, though challenges remain in data security, regulation, and digital literacy. This study aims to provide a concise overview of fintech's role in driving digital economic growth.Keywords : fintech, e-commerce, digital payment, innovation, digital economy